NONLINEAR PROCESSES UNDER THE PHOTOACOUSTIC STUDIES OF CONDENSED MATTER ON THE BOUNDARY OF THE PHASE TRANSITIONS - Sharifov, D. M. (Recent Contributions to Physics, 2009)
The nonlinearity heat equations theoretically are received within the perturbation theory. Theoretical description nonlinear equations of the heat nonlinearity effects, stipulated temperature dependence of thermo physical parameters of the samples. The nonsteady nonlinear problem was solved numerically. The results of the experimental studies on account of the contribution heat nonlinearity effects are analysed.